Ultrasound-Based Assessment in the Diagnosis of Hydronephrosis - Nurmativ Sanjarbek (Genius Journals, 2025)
Hydronephrosis refers to an abnormal enlargement of the renal pelvicalyceal system resulting from obstruction or disturbance of normal urinary drainage. This condition may present in either acute or chronic forms and, if not identified and managed promptly, can progress to permanent renal impairment and eventual kidney failure. Ultrasonography is widely recognized as the primary imaging technique for assessing hydronephrosis due to its broad accessibility, noninvasive nature, affordability, and absence of ionizing radiation. The aim of the present study is to evaluate the clinical significance and diagnostic effectiveness of ultrasound in the identification, differentiation, and follow-up of hydronephrosis across various underlying causes
Keywords: hydronephrosis; ultrasound; renal pelvis